COVID-19 impact on the psychological health of Latinx transgender and non-binary individuals in mainland United States and Puerto Rico: a mixed-methods study - Alíxida Ramos-Pibernus; Sheilla Rodríguez-Madera; Ernesto Rosario-Hernández; Fabián Moreta-Ávila; Julián Silva-Reteguis; Eliut Rivera-Segarra (BMC, 2022)
Abstract Background The COVID-19 pandemic continues to generate an unprecedented impact on all aspects of everyday life across the world. However, those with historically and currently marginalized identities (i.e., gender or ethnicity) who already experience a wide range of structural inequities have been disproportionally impacted. LTNB are a particularly at-risk population as they lie at the intersection of race/ethnicity, gender identity, language, migration status, geographical location, among others, which could further increase their COVID-19 and other health-related risks and disparities. The objective of this study was to examine the impact of key social determinants of health (i.e., gender identity, country, health insurance, employment) among a sample of LTNB individuals. Methods The team implemented a cross-sectional exploratory design with an online survey technique using the secure web platforms REDcap and SurveyMonkey. A total of 133 participants completed the online survey. Most of the sample self-identified as transwomen (38.8%), transmen (26.3%), and non-binary (21.8%) between the ages of 21 to 72. All participants were Latinx living in either Puerto Rico (47.7%) or mainland United States (52.3%). Descriptive statistics, reliability tests, Mann-Whitney and rapid thematic analysis test were conducted. Results Findings show that most participants were always (38.1%) or almost always (33.3%) worried about contracting COVID-19. Individuals living in Puerto Rico reported more difficulties than those residing in the mainland US regarding COVID-19 impact on psychosocial, emotional, and COVID-related thinking. Most participants' answers for the COVID-19 open-ended questions focused on three main domains: income, access to trans-affirmative health care, and coping strategies. Discussion Findings evidence that although most of LTNB participants were negatively impacted by the COVID-19 pandemic in multiple aspects of their lives, those living in Puerto Rico experienced these differently when compared to those in mainland US. More research is needed to understand better the mechanisms and pathways through which this context specifically impacts LTNB health and wellbeing, particularly in Puerto Rico. This study could help shape the public health response taking into account the geographical location and other intersectional identities that play critical roles in the production and reproduction of inequities.